The Impact of Academic Freedom Policies on Critical Thinking Instruction - Shirley Fessel (Park University, 2006)
Critical thinking enjoys almost universal support, except when applied to controversial topics. Yet it is these topics that are often the most effective initiators of critical thinking exercises that improve students' rational approaches to challenging problems. The use of controversial issues to promote critical thinking requires an institutional commitment to academic freedom in order to survive. In some institutional contexts, the most crucial need for critical thinking is the very condition under which it is least likely to be applied. Instead, avoidance of controversy seems to be the predominant policy of institutions fearful of expensive lawsuits or damaging public relations. Several trends are decreasing the likelihood that critical thinking is applied in the classroom to challenging topics: demands for increased accountability from legislatures; scrutiny of adopted content standards; oversight of Internet and other intellectual work of professors affiliated with the universities; student challenges to faculty instruction; and attempts to curtail ideological diversity. This paper describes these current dynamics which erode academic freedom and thus the ability to apply critical thinking to controversial topics. The paper also recommends that institutions and faculty adopt clearly delineated policies related to academic freedom in order to ensure faculty freedom to promote critical thinking. Awareness of how these trends impact the instructional climate enables teachers to design instruction and be more proactive in guaranteeing that critical thinking about controversial topics is able to flourish under academic freedom.